Redes de aprendizaje, aprendizaje en red - Velásquez de Cohen, Gisselle Castro (2014)
The author develops the subject oflearning networks based on her ownexperience in a blended learning course,using this type of networks with studentsof education as a second career andthat where part of the Enseña Peruexperience.